A Current Issue: Analysis of Semantic Perspective Shifting for Meaning in Indonesia Linguistic Context - Ulya Himawati (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2017)
Semantic word is actually a technical term that refers to the study of meaning. Semantics in Indonesian derived from the Greek 'sema' (noun) which means 'sign' or 'symbol'. The verb is 'semaino' which means 'mark' or 'symbolize'. The present study aims to examine the factors that can affect the shift of meaning in Indonesian based on current linguistic context. This study used qualitative research where the intent is to provide a detailed, in-depth description of everyday life. Data was taken from Indonesian language that may address particular themes that may facilitate the use of specific linguistic features. It tends to capture the reality of social life taking place in Indonesia. The result of this study shows that the type of meaning can be distinguished based on some criteria and points of view. The findings indicate that the type of meaning can be distinguished based on semantic types, namely between lexical meaning and grammatical meaning; based on the presence or absence of referents in a word, to distinguish the referential meanings and non-referential; based on the presence or absence of a sense of value in a word, to distinguish the connotative meaning and denotative; based on accuracy of its meaning, to distinguish the meaning of the term or the common meaning and special significance; kind of meaning can also be classified into two types, namely lexical meaning and contextual meaning